Enactive Pragmatism and Ecological Psychology - Crippen, Matthew (Frontiers in Psychology, 2020)
A widely cited roadblock to bridging ecological psychology and enactivism is that the former identifies with realism and the latter with constructivism, which critics charge is subjectivist. A pragmatic reading, however, suggests non-mental forms of constructivism that simultaneously fit core tenets of enactivism and ecological realism. After advancing a pragmatic version of enactive constructivism that does not obviate realism, I reinforce the position with an empirical illustration: P. polycephalum, a communal unicellular organism that leaves slime trails that form chemical barriers that it avoids in foraging explorations. Here, environmental building and sensorimotor engagement are part of the same process, with P. polycephalum coordinating around self-created, affordance-bearing geographies, which nonetheless exist independently in ways described by ecological realists. For ecological psychologists, affordances are values, meaning values are external to the perceiver. I argue that agent-enacted values have the same status and thus do not obviate ecological realism, nor generate subjectivism. The constructivist-realist debate organizes around the emphasis that enactivists and ecological theorists respectively place on the inner constitution of organisms versus the structure of environments. Building on alimentary themes introduced in the P. polycephalum example and also in Gibson’s work, I go on to consider how environment, brain, visceral systems and even bacteria within them enter perceptual loops. This highlights almost unfathomable degrees of mutually modulating internal and external synchronization. It also shows instances in which internal conditions alter worldly configurations and invert values, in Gibson’s sense of the term, albeit without implying subjectivism. My aim is to cut across the somatic focus of enactive constructivism and the external environment-oriented emphasis of ecological realism, and show that enactivism can enrich ecological accounts of value.